HUKUM INTERNASIONAL DAN KAITANNYA DENGAN BENCANA ALAM TSUNAMI - Etty R. Agoes (Sosiohumaniora, 2005)
The massive earthquake of the sea-bed on December 26, 2004, has triggered tsunami in the Indian Ocean and caused large-scale death and destruction in many countries. This disaster has stimulated the international comunity to carry out significant relief efforts. The unparalleled magnitude of this disaster raises questions on whether there is a role of international law, particularly with respect to preparing for, detecting, and responding to natural disasters. This article tries to consider on whether international law has been used in the management of such natural disaster, or whether international law in this area should be more actively been pursued.